Lactobacillus acidophilus ATCC 4356 inhibits biofilm formation by C. albicans and attenuates the experimental candidiasis in Galleria mellonella - Vilela, Simone F. G. [UNESP]; Barbosa, Junia O. [UNESP]; Rossoni, Rodnei D. [UNESP]; Santos, Jessica D. [UNESP]; Prata, Marcia C. A.; Anbinder, Ana Lia [UNESP]; Jorge, Antonio O. C. [UNESP]; Junqueira, Juliana C. [UNESP] (Taylor &francis Inc, 2015)
Probiotic strains of Lactobacillus have been studied for their inhibitory effects on Candida albicans. However, few studies have investigated the effect of these strains on biofilm formation, filamentation and C. albicans infection. The objective of this study was to evaluate the influence of Lactobacillus acidophilus ATCC 4356 on C. albicans ATCC 18804 using in vitro and in vivo models. In vitro analysis evaluated the effects of L. acidophilus on the biofilm formation and on the capacity of C. albicans filamentation. For in vivo study, Galleria mellonella was used as an infection model to evaluate the effects of L. acidophilus on candidiasis by survival analysis, quantification of C. albicans CFU/mL, and histological analysis. The direct effects of L. acidophilus cells on C. albicans, as well as the indirect effects using only a Lactobacillus culture filtrate, were evaluated in both tests. The in vitro results showed that both L. acidophilus cells and filtrate were able to inhibit C. albicans biofilm formation and filamentation. In the in vivo study, injection of L. acidophilus into G. mellonella larvae infected with C. albicans increased the survival of these animals. Furthermore, the number of C. albicans CFU/mL recovered from the larval hemolymph was lower in the group inoculated with L. acidophilus compared to the control group. In conclusion, L. acidophilus ATCC 4356 inhibited in vitro biofilm formation by C. albicans and protected G. mellonella against experimental candidiasis in vivo.
Keywords: Biofilm; Candidiasis; Candida albicans; Filamentation; Probiotic; Galleria mellonella; Lactobacillus acidophilus; ATCC, American type culture collection; YNB, Yeast nitrogen base; MRS, man rogosa and sharpe; PBS, phosphate buffered saline; BHI, Brain heart infusion; CFU, colony-forming unit; SEM, scanning electron microscopy; PAS, periodic acid-Schiff; HE, hematoxylin-eosin; pH, potential hydrogen ion; NIH, National Institutes of Health